Studi Literatur : Pembelajaran Berdiferensiasi dalam Meningkatkan Kemampuan Computational Thinking - Lulu Husni Saih (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to analyze differentiated learning towards increasing computational thinking skills needed by students in the 21st century. This study uses study literature through analysis of the results of several studies. The study collected data related to learning and computational thinking. The results of this study indicate that differentiated learning contributes significantly to improving computational thinking skills, and can be done in mathematics learning. This approach is a relevant strategy in training computational thinking skills so that students can solve problems effectively, efficiently and optimally.